Efficacy of eucalyptus oil (Eucalyptus globulus), sweet orange oil (Citrus sinensis), and grapefruit oil (Citrus paradisi) as bioceramic sealer solvents - Christy Tanujaya; Aryadi; Nadia Hardini (Wolters Kluwer Medknow Publications, 2020)
Background: Essential oil-based gutta-percha solvents have been extensively studied due to their nontoxicity and effectiveness compared to conventional solvents. These solvents can also be used to remove different types of endodontic sealers. Bioceramic-based sealers have become increasingly popular; however, they are difficult to dissolve. Objective: The aim is to examine the differences in efficacy between eucalyptus oil (Eucalyptus globulus), sweet orange oil (Citrus sinensis), and grapefruit oil (Citrus paradisi) as bioceramic sealer solvents. Methods: Thirty-two bioceramic sealer samples were placed in cylindrical stainless steel molds 1.5 mm in height and 8 mm in internal diameter and were placed in an incubator to set. After 72 h, the sealer samples were weighed to obtain their initial weights. Then, they were divided into three groups of ten, which were immersed in 1 ml of eucalyptus, sweet orange, or grapefruit oil for 1 min, and one group of two, used as negative controls. The sealer samples were placed in an incubator for 24 h to dry and weighed once more to obtain their final weights. The differences in weight were calculated and analyzed using one-way analysis of variance. Results: The analysis of the initial and final weight differences of the sealer samples immersed in the three essential oils revealed no statistically significant differences between them. Conclusions: The three essential oils have comparable efficacies as bioceramic sealer solvents.